Study of the influence of carbon nanotubes, graphene, and hybrid buckypaper on the mechanical behavior of PAEK/carbon fiber composites - Feres, Gabriel Damasceno [UNESP]; Ribeiro, Bruno [UNESP]; Costa, Michelle Leali [UNESP]; de Paula Santos, Luis Felipe [UNESP]; Botelho, Edson Cocchieri [UNESP] (My University, 2025)
Carbon fiber-reinforced thermoplastic composites are widely used in the aeronautical industry due to their high mechanical properties and low specific weight. Within the select group of thermoplastic matrices, poly (aryl ether ketone) (PAEK) stands out as a semicrystalline material with high glass transition and melting temperatures. This work aims to evaluate how buckypaper (BP) influences the mechanical properties of the composite PAEK/CF. For this, three types of BPs were made using vacuum filtration. The first one is with carbon nanotubes (CNT), the second is with graphene (GR), and the third is a mix of CNT and GR. The influence of BPs in mechanical behavior was performed by an interlaminar short beam test (ILSS), a compression shear test (CST), and an impulse excitation of vibration. Finally, the presence of BP reduced the mechanical properties of the material due to the low adhesion between matrix and BP. In the ILSS test, it was noted a reduction in interlaminar shear of 16% for CNT BP, 20% for GR BP and 28% for hybrid BP. In the CST, a reduction of 32% for CNT BP, 39% for GR BP and 13% for hybrid BP was observed. On the other hand, the composite with hybrid BP presents a greater increase in Young's Modulus, representing a gain of 13%. Highlights: The vacuum filtration process used to produce BPs was determined. Morphology evaluation of BPs through scanning electron microscopy. Influence of BPs on the mechanical properties of composites. Effect of nanoparticles on the adhesion between matrix and BPs.
Keywords: buckypaper; carbon nanotubes; composite; graphene; PAEK